Fertility and Water Management for Safflower Crop - Bajpai, M R; Parihar, R L; Deshmukh, M T (Annals of Arid Zone, 2016)
Responses of saffiower cultivar Nagpur 7 to the irrigation at 30, 50 and 70 per cent of available soil moisture in 0-60 cm soil layer at various levels of nitrogen and phosphorus were determined for a Coarse loamy Typic Camborthid soil in the semi-arid tract of Rajasthan. Results showed that the commencement of irrigation when available soil moisture level reaches 30 per c nt and fertilization with 80 kg N or 60 kg N plus 60 kg P205/ha resulted in the highest seed yield of 15 to 16 q/ha and consumptive use efficiency of about 38 kg grain per cm of water. In 30% irrigation regime, the consumptive use of water ranged from 37 to 44 cm and the ETI/PE values were of the order of 0.41 to 0.49. Irrigation at the higher soil moisture regimes induced the vegetative growth and reduced seed yields.